1974
DOI: 10.1073/pnas.71.12.4816
|View full text |Cite
|
Sign up to set email alerts
|

The recBC Deoxyribonuclease of Escherichia coli: Isolation and Characterization of the Subunit Proteins and Reconstitution of the Enzyme

Abstract: After dissociation of the E. coli recBC DNase (ATP-dependent DNase) with concentrated NaCl, two subunit proteins were isolated by ion exchange chromatography. Combination and subsequent incubation of the subunits resulted in the appearance of the original DNase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 13 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…Amundsen et al (in press) have demonstrated that this gene encodes a third subunit of the RecBC enzyme that is required for the exonuclease activity of ExoV. The possibility of a third subunit had been suggested previously by the in vitro reconstitution experiments of Lieberman and Oishi (27) and by studies of purified ExoV by Dykstra et al (12). Our mutations affecting plasmid maintenance and the mutations described by Amundsen et al (in press) almost certainly affect the same gene.…”
Section: Discussionmentioning
confidence: 70%
“…Amundsen et al (in press) have demonstrated that this gene encodes a third subunit of the RecBC enzyme that is required for the exonuclease activity of ExoV. The possibility of a third subunit had been suggested previously by the in vitro reconstitution experiments of Lieberman and Oishi (27) and by studies of purified ExoV by Dykstra et al (12). Our mutations affecting plasmid maintenance and the mutations described by Amundsen et al (in press) almost certainly affect the same gene.…”
Section: Discussionmentioning
confidence: 70%
“…Note that all of these phenotypes result from defects in processes involving free DNA ends, which act as the entry points for the RecBCD enzyme. The importance of the RecD subunit was only fully appreciated when it was identified as being a physical component of the "RecBC" holoenzyme required for the exonuclease activity (7,37,105,178). This late discovery was, in part, due to the complexity of interpreting the recD phenotype.…”
Section: Discoverymentioning
confidence: 99%
“…ExoV activity is missing in extracts from either recB or recC mutants. However, one subunit required for ExoV activity, named ax by Lieberman and Oishi, is not eliminated by mutations in either gene (21). Chaudhury and Smith (5) found nuclease-deficient mutations in the vicinity of the recBC genes, and it was later shown that the ExoV activity can be eliminated by mutations in recD while leaving the bacteria proficient for recombination (1,4,5).…”
Section: Methodsmentioning
confidence: 99%
“…The apparent identity of the restriction maps of these plasmids with those of the plasmids used for the initial linear transformation demonstrated that the chromosome had not suffered any gross deletions in this region as a result of allele transfer to the chromosome. DISCUSSION The recB, recC, and recD genes of E. coli code for three polypeptides that make up a single complex protein (1, 21; reviewed in reference 10) containing several enzymatic activities, including a helicase (39) and ExoV (21). In wildtype E. coli, the RecBCD complex promotes homologous recombination, and mutations in recB or recC result in decreased recombination activity and increased sensitivity to UV light.…”
Section: Methodsmentioning
confidence: 99%